Morphology of NdFeB-Type Permanent Magnet Coercivity Enhancement by Heat Treatment Process - Eva Afrilinda; Dagus Resmana Djuanda; Shinta Virdhian; Martin Doloksaribu; Moch Iqbal Zaelana Muttahar; Sri Bimo Pratomo (Universitas Gadjah Mada, 2021)
To understand the morphology of the coercivity enhancement by heat treatment, a commercial sintered NdFeB-type permanent magnet is annealed, and the coercivity is measured by Permagraph. It is shown that the coercivity is increased compared to the initial. Observation by X-Ray Diffraction (XRD) analysis and Scanning Electron Microscope-Energy Dispersive X-ray Spectroscopy (SEM-EDS) is then conducted. The XRD result shows the amount of NdFeB content in the NdFeB-type permanent magnet is increased after heat treatment. The more significant amount of NdFeB content causes higher coercivity. The maximum coercivity, 19 kOe, is achieved at 850 °C of heat treatment temperature, where the NdFeB content is at the highest amount. Microstructural characterizations using SEM-EDS show that at 850 °C of heat treatment temperature, the iron (Fe) content in the grain boundaries is the lowest. It causes higher coercivity. This is due to the magnetically decoupled between NdFeB grains. The decoupling magnet of the NdFeB grains is affected by the Fe content in the grain boundaries. High-temperature heat treatment at 900 and 1050 °C led to the decomposition of NdFeB content in the grains and increased the Fe content in the grain boundaries, which resulted in a substantial reduction of magnetic coercivity.